The U.S. Supreme Court : A Very Short Introduction - Greenhouse, Linda (Oxford, New York Oxford University Press, 2012)
For 30 years, Pulitzer Prize-winning journalist Linda Greenhouse chronicled the activities of the U.S. Supreme Court and its justices as a correspondent for the New York Times. In this Very Short Introduction, she draws on her deep knowledge of the court's history and of its written and unwritten rules to show readers how the Supreme Court really works. Greenhouse offers a fascinating institutional biography of a place and its people--men and women who exercise great power but whose names and faces are unrecognized by many Americans and whose work often appears cloaked in mystery.
Include Index and Illustration
Keywords: United States -- United States. Supreme Court -- Judicial process